Desenvolvimento e produção da soqueira de cana-de-açúcar em função da aplicação de silicato e gesso no plantio - Almeida, Benigno França Amorim de (2013)
This study aimed to evaluate the effect of calcium and magnesium’s silicate and gypsum on the development and production of sugarcane (2nd cycle). The experiment was conducted in the agricultural area belonging to the Capricho Sugar Mill, in the city of Cajueiro, AL. The experimental design was a randomized block in a split-plot with four replications. The treatments consisted of five doses of calcium and magnesium’s silicate (0, 1, 2, 3 and 4 Mg ha-1) (plot) and two levels of gypsum (0 and 1.9 Mg ha-1) (sub -plot). The sub-plot consisted of five rows of 10 m length with a spacing of 1 m between rows. The variety used in the experiment was RB92579. Stem diameter and yield of sugarcane presented increase due to the application of calcium and magnesium’s silicate. The presence of calcium and magnesium’s silicate and gypsum provided greater biomass allocation to the root system and a better distribution in the soil profile. The gypsum provided greater efficiency in water use for plants of sugarcane, and has positively influenced the leaf concentration of calcium, sulfur and silicon.